Legal Consequences of Default in the Franchise Agreement Based on the Case Study (Decision of the Sukoharjo District Court Number 18/Pdt.G/2018/PN Skh) - Kirana, Adelia Nindya; Urbaniasi, Urbaniasi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Franchise, namely an agreement in which one party is given the right to utilize and use intellectual property rights owned by another party in return for a fee based on the terms and sale of goods and or services. This study aims to determine the legal consequences of one of the parties defaulting on the franchise agreement in Decision Number 18/Pdt.G/2018/PN Skh and to find out how to resolve disputes for the franchisor and franchisee in the event of a violation of the franchise agreement. To achieve this goal, the researcher uses normative juridical research, then this normative legal research is based on primary and secondary legal materials. In 2018, the Plaintiff has run the Pinky Guard franchise business, which will be opened in Manado with the defendant. After the plaintiff fulfilled his obligations by making a number of payments, the defendant apparently did not fulfill the plaintiff's rights. So because of this, the defendant can be said to have committed a default because he was unable to fulfill the obligations stipulated in the franchise agreement.